Prudence as an Antidote to Foreign Policy Adventurism: The Case of Turkey in the Syrian Crisis. Issue 2 (3rd April 2023) - Alim, Eray
ABSTRACT: Although International Relations experts acknowledge the importance of prudence in policy-making processes, the term has not been properly operationalised in scholarly works. This work seeks to fill the existing gap in the literature by offering a conceptual and analytical framework of this idea. In addressing the question of what is means to act prudently in foreign affairs, this article takes the foreign policy pursued by Turkey during the Syrian Crisis as its case study. I show that prudence is intimately tied to policy-makers' ability to developing an awareness of situational and historical constraints regarding the issue at hand. And this can only be achieved, provided that policy-makers do not succumb to cognitive bias. Turkey's dismal foreign policy performance in Syria demonstrates that political leaders' failure to appreciate the relevant intrinsic and extrinsic factors in a given foreign policy setting generates the risk of running into costly mishaps.